Stigmergic Optimization - Abraham, Ajith; Grosan, Crina; Ramos, Vitorino (Studies in Computational Intelligence, 2006)
Biologists studied the behavior of social insects for a long time. After millions of years of evolution all these species have developed incredible solutions for a wide range of problems. The intelligent solutions to problems naturally emerge from the self-organization and indirect communication of these individuals. Indirect interactions occur between two individuals when one of them modifies the environment and the other responds to the new environment at a later time. Such an interaction is an example of 'stigmergy'. This book deals with the application of stigmergy for a variety of optimization problems. This volume comprises 12 chapters including an introductory chapter giving the fundamental definitions, inspirations and some research challenges. Important features include a detailed overview of all the stigmergic optimization paradigms, excellent coverage of timely, advanced stigmergic optimization topics, state-of-the-art theoretical research and application developments and chapters authored by pioneers in the field. Academics, scientists as well as engineers engaged in research, development and application of stigmergic optimization will find the comprehensive coverage of this book invaluable.